Effect of Mothers' Educational Supportive Care Program on Pain Intensity and Crying Duration Caused by Colic Pain in Infants Aged 1-5 Months - Maryam Khajeh; Tahereh Sadeghi; Monir Ramezani; Raheleh Derafshi (Mashhad University of Medical Sciences, 2019)
Background: Baby colic is one of the most common digestive problems in infants. Due to its several and unknown causes, colic treatment depends on the parent's individual and social education and support. Aim: This study aimed to determine the effect of mothers' educational supportive care program on the pain intensity and crying caused by colic in infants aged 1-5 months. Method: This study was conducted based on a randomized controlled clinical trial. This study included 88 infants with colic who were referred to a specialized pediatric clinic at a public hospital in eastern Iran. The patients were randomly divided into the intervention and control groups. The educational supportive care program was implemented for eight days and the infant crying duration and frequency were recorded each day. On the other hand, the control group received the clinic routine care. Subsequently, the data were analyzed in SPSS software (Version 21). Results: The two groups were homogeneous in terms of demographic variables (P